Engineering Properties of Limestone Calcined Clay Concrete - Nguyen, Quang Dieu; Castel, Arnaud; Khan, Mohammad Shakhaout Hossain (Journal of Advanced Concrete Technology, 2018)
In this paper, various engineering properties of both fresh and hardened concrete with various limestone and calcined clay contents are investigated. Two concrete grades were considered: 50 MPa or 30 MPa average 28 days compressive strength. A low grade calcined clay was used with about 50% amorphous phase.A reduction in concrete workability was observed with the increase in General Purpose (GP) cement substitution. Superplasticiser was required to obtain a slump equivalent to that of reference GP cement concrete. With 15% GP cement replacement rate, the 28 days compressive strength achieved was superior to that of reference grade 50 MPa concrete, reaching 58 MPa. However, the average 28 days compressive strength reduced significantly with 30% and 45% GP cement replacement, reaching about 35 MPa. Considering concretes with similar 28-day compressive strength, results showed that the 7-day compressive strength was only marginally affected by the limestone and calcined clay substitu-tion. Mercury intrusion porosimetry results revealed that incorporating calcined clay and limestone led to significant refinement of the porosity: increase in the quantity of pores inferior to 0.01µm and reduction in the quantity of coarse pores (with size > 0.1 µm).